A simple and sensitive spectrofluorimetric method for the determination of sodium hexametaphosphate based on the Tb(iii)–TATAB complex. (10th October 2017) - Li, Wei; Ran, Guihua; Zhao, Xijuan; Li, Yuanfang
Abstract : A "turn-off" fluorometric detection method for sodium hexametaphosphate (SHMP) with a terbium(iii ) complex of 4, 4′, 4′′-((1, 3, 5-triazine-2, 4, 6-triyl)-tris(azanediyl))-tribenzoic acid (H3 TATAB) is developed. Abstract : A "turn-off" fluorometric detection method for sodium hexametaphosphate (SHMP) with a terbium(iii ) complex of 4, 4′, 4′′-((1, 3, 5-triazine-2, 4, 6-triyl)-tris(azanediyl))-tribenzoic acid (H3 TATAB) is developed. This approach is simple, convenient, sensitive and successfully applied to the SHMP determination in tea drink samples.